Heterozygous HTRA1 missense mutation in CADASIL-like family disease - Wu,Xiaowei (2018)
The aim of this study was to find related pathogenic genes in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy in (CADASIL)-like patients. The direct sequencing and high-throughput multiplex polymerase chain reaction (PCR) was performed to screen for related genes. The clinical and imaging data of a CADASIL-like patient (the pro-band) and his family members were collected. At first, the known hereditary cerebral vascular genes of the pro-band were screened with direct sequencing to find candidate gene mutations. High-throughput multiplex PCR was then used to analyze the single nucleotide polymorphism of the candidate gene in the family members. The results showed that there was missense mutation of the high temperature requirement protease A1 (HTRA1) gene in the pro-band, which may be a pathogenic factor according to the biological software analysis. The following SNP results revealed that the other family members also had the HTRA1 gene mutation. Thus, the CADASIL-like family disease may be caused by heterozygous HTRA1 gene mutation, which leads to autosomal dominant hereditary cerebral small vessel disease.